Diagnosis of Compound Heterozygous Hb Tak/β-Thalassemia and HbD-Punjab/β-Thalassemia by HbA2Levels on Capillary Electrophoresis - Sitthichai Panyasai (2018)
© 2017, Indian Society of Haematology & Transfusion Medicine. A misdiagnosis of β-thalassemia carrier in samples with Hb Tak and HbD-Punjab, the β-variants, can be a cause of inappropriate genetic counseling thus having a new case of β-thalassemia major. A capillary electrophoresis (CE) is very efficient in separating and quantifying HbA2. In this study, HbA2levels of samples which were doubted for compound heterozygous Hb Tak/β-thalassemia or heterozygous HbD-Punjab/β-thalassemia were measured and compared between CE and high performance liquid chromatography (HPLC). The molecular confirmation for Hb Tak, HbD-Punjab and β-thalassemia codons 17 (A > T), 41/42 (-TCTT), 71/72 (+A) and IVSI-nt1 (G > T) mutations and 3.4 kb deletion were also performed. Based on DNA analysis, 3 cases were diagnosed as compound heterozygous Hb Tak/β-thalassemia and one for HbD-Punjab/β-thalassemia. The elevated HbA2levels were found in all 4 samples with rages of 4.6–7.3% on CE while those were not found on HPLC. Thus, the elevated HbA2measured by CE can be used as a screening parameter for differentiating the homozygote of Hb Tak and HbD-Punjab from the compound heterozygote of these hemoglobinopathies and β-thalassemia.